Double (and triple) Punishment for Peruvians in Argentina, in times of military dictatorships. Between mobilities, deportations and disappearances: Between mobilities, deportations and disappearances - Alvites Baiadera, Angelica (2024)
This article analyzes the experience of Peruvians in Argentina during times of military dictatorships in the 1970s. Both Argentina and Peru operated by monitoring borders and the presence of «potential subversives». We work with a qualitative methodology: key informant interviews and document analysis. The fundamental conclusion is that Peruvians faced a double (and in some cases, triple) punishment (Sayad, 2010). This is manifested in the imposition of the following punishment: (1) penalties through deportation from their home country; (2) condemnation due to their status as non-nationals in Argentina, and (3) sanction for a specific crime, related to «subversive» practices.